Analisis Fundamental Dalam Penilaian Saham Sebagai Keputusan Investasi Di Masa Pandemi Covid-19 - Elsa Amaliana; Dicky Jhoansyah; R Deni Muhammad Danial (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study aims to determine the fundamental analysis in stock valuation as an investment decision during the covid-19 pandemic and the differences calculated from the DDM, PER and PBV methods in the finance sector in the first quarter - fourth quarter 2020. Using a quantitative descriptive research method, with purposive sampling. There are 5 companies that are sampled based on the criteria. The results show that calculated using DDM and PER in the first quarter and fourth quarter, all companies are in the position of undervalued investment decisions, namely buying all company shares. In the second and third quarters, only 1 company was overvalued and the other 4 were undervalued. The investment decision was to sell 1 share and buy 4 company shares. The PBV method for successively every quarter there are 3 undervalued companies and 2 overvalued companies, the decision taken is to buy 3 shares and sell 2 shares. From the results of the comparison of the accuracy between the 3 methods, it shows that the DDM and PBV methods are more accurate because they have low values. Then the results of the one way ANOVA test between the DDM, PER and PBV fundamental analysis methods show the sig value. 0.787 > 0.05, which means that from the three methods there is no significant difference to the market price. Keywords : Fundamental Analysis, Stock Valuation, Comparative, Investment Decision